Seroreversion of hepatitis B surface antigen among subjects with resolved hepatitis B virus infection: A community‐based cohort study. Issue 11 (8th August 2021) - Yeh, Ming‐Lun; Liang, Po‐Cheng; Huang, Ching‐I; Hsieh, Meng‐Hsuan; Lin, Yi‐Hung; Jang, Tyng‐Yuan; Wei, Yu‐Ju; Hsu, Po‐Yao; Hsu, Cheng‐Ting; Wang, Chih‐Wen; Hsieh, Ming‐Yen; Lin, Zu‐Yau; et al.
Abstract: Background and Aim: Hepatitis B virus (HBV) surface antigen (HBsAg) seroreversion usually occurs during immunosuppressive therapy. The risk and factors of HBsAg seroreversion from resolved HBV infection in the general population remained unclear. Methods: This retrospective study enrolled subjects with resolved HBV infection and who had received at least two times of screening in a longitudinal community screening program. HBsAg, hepatitis B surface antibody (anti‐HBs), and hepatitis C virus antibody (anti‐HCV) were tested every time in all subjects. The primary endpoint was HBsAg seroreversion. Results: Of the 7630 subjects enrolled, 5158 (67.6%) subjects had positive anti‐HBs at baseline. HBsAg seroreversion occurred in 84 subjects during 42 815‐person‐year follow‐up with an annual incidence of 0.2% and a 10‐year cumulative risk of 1.9%. Anti‐HBV treatment‐experienced subjects had a significantly higher risk of HBsAg seroreversion than anti‐HBV treatment‐naive subjects (83/310 [26.8%] vs 1/7320 [0.01%], P  < 0.001). Lower rates of positive anti‐HBs and anti‐HCV were observed in anti‐HBV treatment‐experienced subjects who developed HBsAg seroreversion. Both positive anti‐HBs (hazard ratio/95% confidence interval: 0.56/0.348–0.903, P  = 0.017) and positive anti‐HCV (hazard ratio/95% confidence interval: 0.08/0.030–0.234, P  < 0.001) were independent factors of HBsAg seroreversion in anti‐HBV treatment‐experienced subjects. Less than 5% of the HBsAg seroreverters had clinical hepatitis flare at HBsAg seroreversion. The HBsAg titer was low, and only transient reappeared in most of the HBsAg seroreverters. Conclusions: Subjects with resolved HBV infection were at a minimal risk of HBsAg seroreversion, unless with prior anti‐HBV treatment experience. Fortunately, even with a reappearance of HBsAg, it was transient and clinically non‐relevant.